Taxation, SMEs and Entrepreneurship - Chen, Duanjie (OECD Publishing, 2002)
This paper discusses the implications of tax policy for the growth of entrepreneurship and small and medium-sized enterprises (SMEs). Some existing features of OECD tax systems are biased against entrepreneurs and small firms. For instance, double taxation of distributed corporate profits can discourage incorporation of small firms while it can also favour debt over equity financing, the latter most required by SMEs. Conversely, a number of OECD countries have features in their tax systems that favour selfemployed individuals and SMEs to encourage growth. These include lower corporate income tax rates, exemptions from value-added taxes and investment tax credits. It is, however, not clear that the benefits of preferential tax treatment of self-employed individuals and SMEs outweigh the costs of moving away from tax neutrality. There are a number of areas where OECD governments can improve the tax climate for small firms and entrepreneurs. They can reduce progressivity in personal ...
Keywords: Science and Technology